Precision in Spinal Cord Injury Research: A Novel Electromagnetic Impactor for a Consistent Porcine Model - Leonard Steger; Abdul Karim Ghaith; Carly Weber-Levine; Kayla Robinson; Christina Krueger; Constantin Smit; Siddharth Krishnan; Kelley M. Kempski Leadingham; Daniel Davidar; Denis Routkevitch; Kelly Jiang; Victor Quiroz; et al. (Annals of Biomedical Engineering, 2025)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Stripes, jewels and spines: further investigations into the evolution of defensive strategies in a chemically defended gecko radiation ( Strophurus , Diplodactylidae) - Stuart V. Nielsen; Paul M. Oliver; Rebecca J. Laver; Aaron M. Bauer; Brice P. Noonan (Zoologica Scripta, 2016)
The geckos in the genus Strophurus (Diplodactylidae) are one of only two squamate lineages with specialized caudal defensive glands. Many species in this genus also have distinctive caudal ornamentation combined with bright and/or contrasting colour pattern elements on the iris, tail and especially the lining of the mouth that are hypothesized to be adaptations for specialized (e.g. deimatic) defensive functions. We present the first multilocus, phylogenetic analysis of the biogeography and evolution of all recognized taxa of Strophurus . Contrary to previous phenotypic and ecological assessments, our phylogenetic analyses delineate four divergent lineages. Three lineages are relatively small (snout‐vent length [ SVL ] 40–60 mm), species‐poor ( SVL 60–90 mm), possesses precloacal pores and shows extensive variation in caudal ornamentation and often bright and/or contrasting eye, tail and mouth colouration. The three less diverse lineages have smaller distributions and tend to be associated with spinifex (e.g. Triodia ) hummock grasses or rocks, whereas the fourth lineage is much more widespread (including multiple biomes) and consistently reported to utilize more exposed diurnal microhabitats on shrubs and trees. Biogeographical analyses also indicate that – in contrast to many other Australian radiations – the arid biome is the ancestral area of occupation for Strophurus , with multiple inferred shifts into surrounding sclerophyll and monsoon biomes. This study emphasizes that – independent of caudal defensive glands – it appears to be a shift in microhabitat use that correlates with the accumulation of bright and contrasting colouration elements, secondary sexual characters and the widest geographic distribution.

The size of savannah Africa: a lion’s (Panthera leo) view - Jason Riggio; Andrew Jacobson; Luke Dollar; Hans Bauer; Matthew Becker; Amy Dickman; Paul Funston; Rosemary Groom; Philipp Henschel; Hans de Iongh; Laly Lichtenfeld; Stuart Pimm (Biodiversity and Conservation, 2013)